Comprehensive study on flame retardant polyesters from phosphorus additives. (September 2018) - Salmeia, Khalifah A.; Gooneie, Ali; Simonetti, Pietro; Nazir, Rashid; Kaiser, Jean-Pierre; Rippl, Alexandra; Hirsch, Cordula; Lehner, Sandro; Rupper, Patrick; Hufenus, Rudolf; Gaan, Sabyasachi
Abstract: In this work we have performed a comprehensive study on synthesis, processing, detailed material characterization and preliminary assessment of toxicity of relatively new flame retardant (FR) additives as a key for developing environmentally friendly fire safe polyesters. Two 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) based FR additives were synthesized using principles of green chemistry and incorporated via thermal processing in high temperature polyesters such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). The green synthesis strategies included (i) the use of N-chlorosuccinimide as a sustainable chlorinating agent for DOPO and (ii) a solvent and catalyst free microwave-assisted synthesis. Atomistic molecular dynamics (MD) simulations were employed in order to calculate the solubility parameters of these additives so as to estimate their compatibility in the polyesters. Detailed rheological measurements of the polyester/FR blends were carried out and the results indicated a clear difference in all three additives tested. Based on these analyses, 6H-dibenz[c, e][1, 2]oxaphosphorin, 6-[(1-oxido-2, 6, 7-trioxa-1-phosphabicyclo[2.2.2]oct-4-yl)methoxy]-, 6-oxide (DOPO-PEPA) exhibited the highest compatibility with both polyesters and their blends and showed the highest thermal-oxidative stability guaranteeing stable and steady processing at high temperatures. All polyester/FR formulations exhibited higher flame retardancy compared to the virgin polyesters in the small scale fire tests. The FR additives were evaluated for their potential toxicity using a well-established in vitro platform. Our results indicate no acute cytotoxic potential for all FRs analyzed in two different cell types (the human lung epithelial cell line A549 and macrophages derived from the monocytic cell line THP-1) and under the chosen experimental conditions. Highlights: New DOPO based flame retardant (FR) additives were synthesized using principles of green chemistry. Molecular dynamics simulations confirmed their compatibility in the polyesters. DOPO-PEPA exhibited the highest thermal-oxidative stability and compatibility with both polyesters. All polyester/FR formulations exhibited higher flame retardancy compared to the virgin polyesters. Well-established in vitro experiments indicate no acute cytotoxic potential for all FRs analyzed.